(untitled) (World Bulletin of Public Health, 2022)
Background Tachypnia and dyspnoea of ICU covid 19 patients with more than 60% lung involvement result in great patient discomfort ,hope loss, air hunger and respiratory fatigue followed by generalised fatigue with downgrading cases. Those patients initially put on tight NIV oxygenated mask fitness enhanced by more breathing pressure than simple O2 masks , doing so with merely ventilating them depending on their own respiratory pattern results in some sort of improvement in the above patient symptoms but if those patients fail to response to the overall treatment measures, besides, their families refuse endotracheal tube placement then we can’t put them at the risks of more breathing pressures than usual because of possible fatal pneumothorax and /or emphysema